Poor man's feast [large type] : a story of comfort, desire, and the art of simple cooking - Altman, Elissa (Center Point Large Print, 2016)
"The author of the popular Poor Man's Feast blog chronicles her lifelong relationship with all things culinary and the transformation she experiences -- from culinary trend-aholic to a champion of simplicity -- when she finally finds love. Short chapters sprinkled with recipes show that living and eating well are much simpler than we might think"--